Encouraging Self-Regulation in an Online University Course for Preservice Teachers: An Intervention Study: An Intervention Study - Arnesen, Karen T.; Leary, Heather; Graham, Charles R.; McMurry, Alison I (Online Learning, 2025)
Abstract Although self-regulation has long been seen as an important educational concept, we know little about how to foster it in higher education online student populations. This research addressed this lack by investigating an SR intervention introduced into an online course, based on weekly student goal-setting and self-reflection. Findings, using both qualitative and quantitative data from surveys, weekly reflections, final exams, and interviews, indicated that while progress in developing SR habits was not consistent, it was steady as students set goals and reflected weekly on their progress (or lack of it). Weekly self-evaluation helped students become more self-aware as they analyzed why they failed or succeeded in the previous week. This awareness helped them set more specific and meaningful goals. The research also demonstrated the value of qualitative data and the weaknesses of survey data, which the qualitative data helped overcome. Students demonstrated that a weekly goal-setting and self-evaluation process could impact their self-regulation abilities in positive and influential ways. Keywords: Self-regulation; online education; higher education; intervention; preservice teachers; qualitative; survey